Site occupation dynamics of early modern humans at Misliya Cave (Mount Carmel, Israel): Evidence from the spatial taphonomy of faunal remains. Issue 143 (June 2020) - Yeshurun, Reuven; Malkinson, Dan; Crater Gershtein, Kathryn M.; Zaidner, Yossi; Weinstein-Evron, Mina
Abstract: Space use in Middle Paleolithic (MP) camps has been suggested as a source of information on the intensity and repetition of occupations and, by extension, of demographics. In the Levant, clear evidence for differential intrasite use and maintenance was important in viewing the late MP Neanderthal sites as base camps inhabited for a significant duration, relative to the Early MP (EMP). We test this model with the rich faunal assemblage from the EMP (>140 ka) site of Misliya Cave, Mount Carmel, Israel. Excavations in Misliya yielded a large and diverse lithic assemblage, combustion features, and a modern human maxilla, together with a large archaeofaunal assemblage that we use as a spatial marker. We analyzed the distribution of bone items with variable taphonomic properties (anthropogenic, biogenic, and abiotic bone-surface modifications) in a hearth-related context, both by comparing grid squares and point patterns. Both analyses are largely congruent. They indicate repeated and consistent use of the site's space that includes hearth-related consumption activities and peripheral activities further away, albeit with little evidence for site maintenance. Thus, the Misliya results display a mixed signal of clear around-the-fire pattern and differential space use in the EMP that is reminiscent of the much later MP sites in the Levant, but without the more elaborate camp maintenance. More case studies and detailed proxies are needed before we can fine-tune our understanding of camp structure in the Levantine MP and its bearing to site occupation dynamics.